Assessing motivations and perceptions of stakeholders in urban agriculture: a review and analytical framework. Issue 2 (4th May 2021) - Di Fiore, Gianluca; Specht, Kathrin; Zanasi, Cesare
ABSTRACT: Interest in the adoption of urban agriculture (UA) has grown in recent years. The compatibility of UA with the urban social context, in particular with urban stakeholders' attitudes, is crucial for its successful implementation and represents one of the key factors influencing its development. To this end, a literature review on different approaches to analysing stakeholders' and farmers' perceptions of UA is performed. The paper identifies the main approaches to assessing these aspects and designs an integrated framework to support the development of context-tailored analytical approaches for UA drivers' and stakeholder perceptions. The study aims to address and solve potential conflicts between UA practitioners and urban stakeholders and adapt the implementation of UA to contextual factors. This increases the possibility of developing successful UA strategies that meet the challenges currently facing urban food systems.